Improved survival after allogeneic transplantation for acute lymphoblastic leukemia in adults: a Danish population-based study. Issue 2 (28th January 2022) - Gjærde, Lars Klingen; Rank, Cecilie Utke; Andersen, Mette Klarskov; Jakobsen, Lasse Hjort; Sengeløv, Henrik; Olesen, Gitte; Kornblit, Brian; Marquart, Hanne; Friis, Lone Smidstrup; Petersen, Søren Lykke; Andersen, Niels Smedegaard; Nielsen, Ove Juul; et al.
Abstract: We investigated trends of survival in a population-based cohort study of all 181 adults who received HCT for ALL in Denmark between 2000–2019. Patients had a median (min–max) age of 36 (18–74) years at HCT and were followed for a median of eight years. Overall survival (OS) improved over time with an estimated 2-year OS of 49% (CI 27–66%) in year 2000 versus 77% (CI 59–88%) in year 2019. More patients achieved cure over time (OR for cure per year 1.07, CI 1.00–1.15), while the rate of death in non-cured patients remained stable (HR of excess mortality per year 0.99, CI 0.93–1.06). Relapse decreased over time (HR 0.92 per year, CI 0.87–0.98), whereas non-relapse mortality did not change notably (HR 0.98 per year, CI 0.93–1.04). In conclusion, survival after HCT in adults with ALL has improved over the past two decades, primarily due to more patients achieving cure.